Artropodofauna de interesse forense no cerrado do município de Uberlândia, MG: abundância relativa, diversidade e sucessão entomológica - Rosa, Thiago Augusto (2007)
Necrophagous arthropods can be auxiliary to elucidate crimes and its use is gaining great importance, in the lost years. Among the various applications of entomologic data, the estimative of the postmortem interval (PMI) of the corpse is highlighted. Some studies are being carried out aiming know the species of forensic importance and the standard of insects succession during the bodies´ process of decomposition. Generally the data obtained in different regions are not of reciprocal application because differences in physical factors and necrophagous community in each region,. In Cerrado Bioma, studies on Forensic Entomology for knowledge are still at the beginning. This work was carried out in the natural areas of Cerrado in Uberlândia municipality, MG. The study emphasized the diversity, abundance of the species, as well as the patterns of entomology succession throughout the decomposition process of pig carcasses exposed in this environment. The experiments were carried out at two profiles of Cerrado ( campo sujo and cerrado stricto sensu ) pertaining to Reserva Ecológica do Clube de Caça e Pesca Itororó de Uberlândia, in the dry (2005) and humid (2006) periods of the year. Pig carcasses, Sus scrofa (Linnaeus) of 10 kg were used. They were exposed in the traps adapted for collection of the adult and immature insects. The dry period and the campo sujo profile presented greater number of individuals. A total of 161.143 adult insects was collected, being Diptera the most abundant (80.2%) followed by Coleoptera (8.8%). By having used the carcasses as breeding substratum, these orders are considered the most important of the forensic point of view. Breed Calliphoridae presented greater number of emerged adults and were represented mainly by Chrysomya albiceps. Lucilia eximia and Peckia (Pattonella) intermutans are potential forensic indicators of vegetacional profile and seasonality. The duration of the decomposition process differed between vegetation types and periods of the year. Relative humidity associated to pluviosity are the physical factors responsible for this difference.